Map of Social-Cultural Dakwah Communications (Da'i) and Audience (Mad'u) in Padang City - Wakidul Kohar; Muhammad Aqil; Danil Folandra (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2022)
This study aims to describe the map of da'wah in the city of Padang, focusing on studies on religious groups. In addition, the research explores the patterns of interaction and communication between da'i and mad'u in the city of Padang. The research location was carried out at four points, namely the Districts of Koto Tangah, Nanggalo, South Padang, and Bungus Teluk Kabung. The research was conducted with a qualitative approach. Data collection techniques were obtained through observation, interviews, and documentation. Key informants in the study consisted of preachers, religious leaders, and the community (mad'u). The findings show that religious groups spread over four sub-districts, such as Muhammadiyah, NU, and Perti. In other groups, such as in Padang Selatan, the Tablighi Jamaat and several Tarekat groups were found. The pattern of relations between da'i and mad'u in four sub-districts is in the form of relations between organizations, egalitarian or neutral. While the interaction between the two shows a friendly, mutually promoting, and neutral attitude. The implications of the research are providing information and guidance for religious communicators in analyzing the socio-cultural conditions of the mad'u group in designing messages and da'wah programs that can drive social change.